Adapting early childhood education interventions to contexts: Lessons and challenges of using different evaluation designs. (September 2022) - Treviño, Ernesto; Godoy, Felipe
Abstract: This paper analyzes the experience of three waves of implementation of UBC, an intervention to improve early childhood education quality in schools serving disadvantaged children in Chile. It delves on the notions of context as a primary source of information to adapt and improve educational programs in order to adjust to local needs. The results show that adapting to context improves both the quality of classroom interactions and child outcomes. The paper discusses the tensions between experimental and quasi-experimental methods in assessing these types of programs. Highlights: Experimental designs have the advantage of producing causal inferences, but their adaptation to contexts is limited. Quasi-experimental designs reduce the threats on the inferences but allow for adjustment during implementation. Studies in education need to ponder both options depending on their purposes.